Natural fibre filament for Fused Deposition Modelling (FDM): a review - Razali, Nadlene; Dhar Malingam, Sivakumar; Jamadi, Aida Haryati; Mohammad Taha, Mastura; Lazim, Yusriah; Rushdan, Ahmad Ilyas (Taylor & Francis Group, 2021)
Fused Deposition Modelling (FDM) gets the most attention in development and manufacturing industries. The demand for FDM in industries increases gradually over time and attracts many researchers to enhance the quality of the FDM’s fillers. The most popular filler reinforcements in use are synthetic or carbon fibre. However, these fibres are harmful to the environment. To overcome the issue and replace the current fibres and achieve the bio-composites filler, researchers suggested using natural fibre to replace the synthetic and carbon fibres as the reinforcement, which is also combined with bio-polymer matrix such as thermoplastics as the polymer matrix in FDM’s industries. Many experiments and tests are conducted to prove the capability of the natural fibre as the main material in composite industries. FDM is a world-wide technology that aims to be environmentally friendly, thus, this paper focuses on biodegradable fillers for FDM.